Band-gap and strain engineering in GeSn alloys using post-growth pulsed laser melting. (8th February 2023) - Steuer, O; Schwarz, D; Oehme, M; Schulze, J; Mączko, H; Kudrawiec, R; Fischer, I A; Heller, R; Hübner, R; Khan, M M; Georgiev, Y M; Zhou, S; et al.
Abstract: The pseudomorphic growth of Ge1− x Sn x on Ge causes in-plane compressive strain, which degrades the superior properties of the Ge1− x Sn x alloys. Therefore, efficient strain engineering is required. In this article, we present strain and band-gap engineering in Ge1− x Sn x alloys grown on Ge a virtual substrate using post-growth nanosecond pulsed laser melting (PLM). Micro-Raman and x-ray diffraction (XRD) show that the initial in-plane compressive strain is removed. Moreover, for PLM energy densities higher than 0.5 J cm −2, the Ge0.89 Sn0.11 layer becomes tensile strained. Simultaneously, as revealed by Rutherford Backscattering spectrometry, cross-sectional transmission electron microscopy investigations and XRD the crystalline quality and Sn-distribution in PLM-treated Ge0.89 Sn0.11 layers are only slightly affected. Additionally, the change of the band structure after PLM is confirmed by low-temperature photoreflectance measurements. The presented results prove that post-growth ns-range PLM is an effective way for band-gap and strain engineering in highly-mismatched alloys.